Chemical Compositions of Metals in Bhasmas and Tibetan Zuotai Are a Major Determinant of Their Therapeutic Effects and Toxicity. (10th January 2019) - Liu, Jie; Zhang, Feng; Ravikanth, Velagapudi; Olajide, Olumayokun A.; Li, Cen; Wei, Li-Xin
Abstract : Minerals are alchemically processed as Bhasmas in Ayurvedic medicines or as Zuotai in Tibetan medicines. Ayurveda is a knowledge system of longevity and considers the mineral elixir made from "nature" capable of giving humans perpetual life. Herbo-metallic preparations have a long history in the treatment of various diseases in India, China, and around the world. Their disposition, pharmacology, efficacy, and safety require scientific evaluation. This review discusses the Bhasmas in Ayurvedic medicines and Zuotai in Tibetan medicines for their occurrence, bioaccessibility, therapeutic use, pharmacology, toxicity, and research perspectives. A literature search on Mineral, Bhasma, Ayurvedic medicine, Zuotai, Tibetan medicine, and Metals/metalloids from PubMed, Google and other sources was carried out, and the relevant papers on their traditional use, pharmacology, and toxicity were selected and analyzed. Minerals are processed to form Bhasma or Zuotai to alter their physiochemical properties distinguishing them from environmental metals. The metals found in Ayurveda are mainly from the intentional addition in the form of Bhasma or Zuotai. Bhasma and Zuotai are often used in combination with other herbals and/or animal-based products as mixtures. The advanced technologies are now utilized to characterize herbo-metallic preparations as Quality Assurance/Quality Control. The bioaccessibility, absorption, distribution, metabolism, and elimination of herbo-metallic preparations are different from environmental metals. The pharmacological basis of Bhasma in Ayurveda and Zuotai in Tibetan medicines and their interactions with drugs require scientific research. Although the toxic potentials of Bhasma and Zuotai differ from environmental metals, the metal poisoning case reports, especially lead (Pb), mercury (Hg), and arsenic (As) from inappropriate use of traditional medicines, are increasing, and pharmacovigilance is desired. In risk assessment, chemical forms of metals in Bhasma and Zuotai should be considered for their disposition, efficacy, and toxicity.